Pengaruh Suhu Air dan Lama Waktu Perendaman Beberapa Jenis Sayuran Daun pada Proses Crisping - SUPARTHA UTAMA, I MADE; AYU NOCIANITRI, KOMANG; RINA PRATIWI PUDJA, IDA AYU (AGRITROP, 2012)
The primary cause of wilting in leafy vegetables after harvesting is high intensity of transpiration process through natural openings (stomata, hidatoda and lenticels). The mechanism of closing and opening of those natural openings is affected by the temperature of the environment. Under high external temperature, the stomata tend to open and vice versa. It is possible to diffuse water into the produce to give a vigorous effect by controlling the external temperature and moisture. The process is normally called crisping. The aim of this experiment was to study the effectiveness of crisping in order to give vigorous and freshness effects to four different leafy vegetables, namely lettuce, kangkung, leeks and chinese cabbage compared to those without crisping. The crisping process was involving the immersion of produce in three different water temperatures (30, 40 and 50oC) combined with different lengths of immersion times (1, 3, 5 and 7 minutes) and continued by immediate movement of produce to low temperature (5±2oC) and stored for 12 hrs before placing and displaying at the show case under temperature of 10±2oC. Produce treated as controls were provided without immersion in the warm water and stored at room temperature, and other was also placed at the show case. The result shows that the effectiveness of crisping depended upon the physical structure or morphology of the respective vegetables. In general, the water temperatures of 30 and 40oC and combined with the lengths of immersion time of 1-3 minutes were effective to improve the freshness and vigorousness of lettuce and leeks, while 7 minutes immersion was effective for kangkung and Chinese cabbage.
Keywords: Crisping, leafy vegetables, lettuce, kangkung, leeks and Chinese cabbage.